2009
DOI: 10.1016/s1875-9572(09)60079-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Growth From Foot Length in Taiwanese Neonates

Abstract: Our study demonstrated a significant degree of correlation between FL and BBW, BBL and HC. However, it did not reliably estimate BBW, BBL, or HC-the three anthropometric indices were weakly correlated (r<0.5) with FL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Compared to our study, preterm infants had shorter foot measurements, and term babies had longer foot measurements (12). In a retrospective study performed in Taiwan, compared to the study in which the foot length was measured with the footprint, our study found that the foot length was 1.7 cm longer in term infants (13). Our foot length results were also smaller when compared to the standardized study by Merlob et al (9).…”
Section: Discussioncontrasting
confidence: 65%
“…Compared to our study, preterm infants had shorter foot measurements, and term babies had longer foot measurements (12). In a retrospective study performed in Taiwan, compared to the study in which the foot length was measured with the footprint, our study found that the foot length was 1.7 cm longer in term infants (13). Our foot length results were also smaller when compared to the standardized study by Merlob et al (9).…”
Section: Discussioncontrasting
confidence: 65%
“…[30] The mean birth weight of children born to mothers with daytime jobs in this study (3271.7 g) was similar to that of Taiwanese neonates in the general population. [31] This study demonstrated that the newborns of mothers exposed to long-term and relatively drastic rotating shift schedules were significantly lighter (250 g) than those of other female workers. This difference is substantially greater than the 117 g decrease found in a large-scale study of similar aged Chinese female shift workers (mean age 28.7 years) who worked on a 3-shift/8-hour schedule in traditional factories.…”
Section: Discussionmentioning
confidence: 66%
“…Six separate research studies from UK, India, Nepal and Taiwan have reported on studies to investigate newborn foot length as a screening tool for small babies, showing consistent foot length cut-offs for identifying small babies across different countries (Figure 1) [11-16]. Moreover, despite having different aims and objectives, five out of six of the studies concluded that for high risk babies born at home, measuring foot length in the community may have advantages over other methods.…”
Section: Introductionmentioning
confidence: 99%
“… Recommended newborn foot lengths for identification of small babies reported in peer-reviewed literature [11-16]. …”
Section: Introductionmentioning
confidence: 99%